Urine levels of 5-aminoimidazole-4-carboxamide riboside (AICAR) in patients with type 2 diabetes - Mendler, Michael; Kopf, Stefan; Gröner, Jan; Riedinger, Christin; Fleming, Thomas; Nawroth, Peter Paul; Okun, Jürgen G. (Acta diabetologica, 2018)
AIMS: 5-Aminoimidazole-4-carboxamide riboside (AICAR) is an endogenous activator of AMPK, a central regulator of energy homeostasis. Loss and/or reduction of AMPK signaling plays an important role in the development of insulin resistance in type 2 diabetes. The loss of AMPK in diabetes could be due to a loss of AICAR. The aim of this study was to characterize urine levels of AICAR in diabetes and determine whether an association exists with respect to late complications, e.g., retinopathy, nephropathy and neuropathy. - METHODS: Urine AICAR was measured by liquid chromatography tandem mass spectrometry in 223 patients consisting of 5 healthy controls, 63 patients with pre-diabetes, 29 patients with newly diagnosed type 2 diabetes and 126 patients with long-standing type 2 diabetes. For statistical analyses, nonparametric Kruskal-Wallis test, one-way ANOVA and multivariate regression analysis were performed to investigate the associations of urinary AICAR excretion within different groups and different clinical parameters. - RESULTS: The mean urine AICAR for all 223 patients was 694.7 ± 641.1 ng/ml. There was no significant difference in urine AICAR between the control and patients with diabetes (592.3 ± 345.1 vs. 697.1 ± 646.5 ng/ml). No association between any of the biochemical and/or clinical parameters measured and urine AICAR was found, with the exception of age of patient (R = - 0.34; p < 0.01) and estimated glomerular filtration rate (R = 0.19; p = 0.039). These results were confirmed additionally by linear regression analysis. - CONCLUSIONS: Clinical diabetes is not associated with a change in endogenous AICAR levels. Loss of AICAR may therefore not be a mechanism by which AMPK signaling is reduced in diabetes.
Gesehen am 30.03.2020